2022
DOI: 10.3390/cancers14194919
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Malignancy Risk in Multiple Myeloma from 1975 to 2018

Abstract: As the survival times for multiple myeloma (MM) patients continue to extend, the risk of a second primary malignancy (SPM) among MM survivors has become a topic of increasing concern within the medical community. The Surveillance, Epidemiology, and End Results (SEER) 9 Registry Database was used to evaluate the risk and survival of SPM among MM survivors from 1975 to 2018. The standardized incidence ratio (SIR), absolute excess risk (AER), and cumulative incidence (CMI) of SPM for MM risk were calculated. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Interestingly, in contrast to their frequencies in the general population [22], but in line with prior studies that evaluated SPMs in patients with MM [23], the most common hemato-SPMs were AML and MDS rather than NHL [24,25], caused by the progression of occult BM clonal hematopoiesis(ref) and/or treatment-related toxicity, mainly AutoHCT [17].…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, in contrast to their frequencies in the general population [22], but in line with prior studies that evaluated SPMs in patients with MM [23], the most common hemato-SPMs were AML and MDS rather than NHL [24,25], caused by the progression of occult BM clonal hematopoiesis(ref) and/or treatment-related toxicity, mainly AutoHCT [17].…”
Section: Discussionsupporting
confidence: 72%
“…Among IMiDs, lenalidomide has been indicated consistently as a possible contributor to SPM development in several large-scale randomized studies and meta-analyses [5,[20][21][22][23][24]. In our research, in the same context, lenalidomide might be an attributable factor for SPM because lenalidomide had been introduced to the clinical practice with being covered by NHIS in Korea since the year 2014.…”
Section: Discussionmentioning
confidence: 68%
“…Turgutkaya et al showed five (1.6%) SPM cases among 310 symptomatic Turkish MM patients, and these patients had shorter survival [ 7 ]. Wang et al collected data from the SEER 9 Registry Database (1973–2018) on 43,825 newly diagnosed MM patients and found that a total of 3101 (7.1%) patients developed 3407 SPMs [ 28 ]. They also showed that age, race, sex, and time of diagnosis were significant factors for the risk of developing SPM, and that patients with SPM had a 1.4-fold higher risk of mortality.…”
Section: Discussionmentioning
confidence: 99%